The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1128/jvi.01088-18
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Membrane Fusion Inhibitors with Extremely Potent Activity against Human Immunodeficiency Virus Type 1 (HIV-1), HIV-2, and Simian Immunodeficiency Virus

Abstract: T-20 (enfuvirtide) is the only membrane fusion inhibitor available for the treatment of viral infection; however, it has low anti-human immunodeficiency virus (anti-HIV) activity and a low genetic barrier for drug resistance. We recently reported that T-20 sequence-based lipopeptides possess extremely potent and efficacies (X. Ding, Z. Zhang, H. Chong, Y. Zhu, H. Wei, X. Wu, J. He, X. Wang, Y. He, 2017, J Virol 91:e00831-17, https://doi.org/10.1128/JVI.00831-17; H. Chong, J. Xue, Y. Zhu, Z. Cong, T. Chen, Y. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 54 publications
(69 reference statements)
4
39
0
Order By: Relevance
“…The epitope of Ab QA255.067 (from 952-606; LLGIWGCSGKLICTT), identified by binding to similarly constructed VLPs (32), is near 2C6 but is also dependent on the disulfide bridge of the C-C loop sequence. Besides the fusion peptide-targeting Abs, 2C6 also maps near the hydrophobic pocket targeted by enfuvirtide (T20) and other fusion inhibitors in development (33). A number of our QtAbs can interfere with enfuvirtide in a fusion assay, but 2C6 failed to interfere with the function of T20 (34).…”
Section: Discussionmentioning
confidence: 98%
“…The epitope of Ab QA255.067 (from 952-606; LLGIWGCSGKLICTT), identified by binding to similarly constructed VLPs (32), is near 2C6 but is also dependent on the disulfide bridge of the C-C loop sequence. Besides the fusion peptide-targeting Abs, 2C6 also maps near the hydrophobic pocket targeted by enfuvirtide (T20) and other fusion inhibitors in development (33). A number of our QtAbs can interfere with enfuvirtide in a fusion assay, but 2C6 failed to interfere with the function of T20 (34).…”
Section: Discussionmentioning
confidence: 98%
“…Cholesterylated inhibitors exhibit extremely potent activity against HIV-2 and SIV isolates. In the previous works, we also demonstrated that the fatty acidconjugated inhibitors possess highly potent activity against HIV-2 and SIV isolates (25)(26)(27). Here, we also characterized the inhibitory activities of cholesterol-modified inhibitors in comparison to T-20, LP-80, and C34-Chol.…”
Section: Resultsmentioning
confidence: 56%
“…By adding a cholesterol group to the template peptide C34, the lipopeptide C34-Chol was reported as the most potent HIV-1 fusion inhibitor (17), and it is currently being evaluated in clinical trials (28). However, we recently found that the T-20-based sequence is a more efficient template, resulting in the inhibitors conjugated with a fatty acid group (24)(25)(26)(27). To create an ideal candidate for clinical development and to exploit the structure-function relationship of diverse lipopeptide inhibitors, here we generated a group of T-20 backbone-based fusion inhibitors by cholesterol conjugation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations